Analisis Teori Hegemoni Antonio Gramsci terhadap Pengaruh TikTok dan YouTube dalam Membentuk Opini Publik : Influencer sebagai Intelektual Organik Fashion - Rangga Jastian Saputra; Muhammad Nazrul Farizi; Rifma Ghulam Dzaljad (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the role of fashion and lifestyle influencers on TikTok and YouTube as organic intellectuals from the perspective of Antonio Gramsci's Theory of Hegemony. This study uses a qualitative approach using Norman Fairclough's Critical Discourse Analysis (CDA). Data were collected through digital observation, content documentation, and a literature review of influential social media content. The findings indicate that influencers function as agents of cultural hegemony by shaping public opinion through digital aesthetic representations, parasocial relationships, and the reproduction of consumerist ideology. Through personal narratives, idealized visuals, and the support of platform algorithms, influencers build social consciousness that encourages audiences to accept certain lifestyle standards as normal and desirable. This study concludes that TikTok and YouTube have become new arenas of hegemony that significantly influence the formation of culture and consumption behavior in digital society, especially among Generation Z.